On the dynamic response of additively manufactured 316L - Smith, LC; Chapman, DJ; Hooper, PA; Whiteman, G; Eakins, DE (AIP Publishing, 2018)
Understanding the dynamic mechanical behaviour of Additively Manufactured (AM) materials is important when designing components for real-world applications. A series of Taylor tests were carried out on AM and conventionally manufactured 316L stainless steel to evaluate differences in mechanical behaviour arising from manufacturing process. AM specimens were produced with a Renishaw AM250 selective laser melting machine. The influence of the layered, anisotropic, non-homogeneous microstructure of AM materials was investigated by manufacturing samples parallel and perpendicular to the build direction, comparing both orientations to conventionally manufactured samples. Taylor tests were conducted in a reverse anvil-on-rod configuration with photon doppler velocimetry and high speed imaging fielded. A clear difference was observed in target rear surface velocity profiles between additively manufactured vertical, horizontal and conventionally manufactured samples. Calculated estimates for dynamic compressive yield stress were in agreement with trends observed in quasi-static and dynamic regimes [1, 2].